The Causes of the First British Invasion of Afghanistan in 1839 - Alami, Ahmad Wali; Akbari, Qais (Journal of Social Sciences - Kabul University, 2025)
In 1839, the British, as a Western power, invaded Afghanistan. The aim of this research is to identify the factors behind this invasion. This study is significant in several ways, including its contribution to a better understanding of British policy toward the region, especially Afghanistan. It also highlights Afghanistan’s status and value as a sensitive area in nineteenth-century world politics, offering important lessons for policymakers. Given Afghanistan’s geographic position, which has always ensured its relevance in regional politics, the findings show that several key factors contributed to the British invasion In 1839: the growing influence of Russia in Afghanistan, the actions of Amir Dost Mohammad, shifts in British policy, and issues within Afghanistan’s domestic politics. The research was conducted using a review method.